A novel model for studying baculovirus infection process - Lindenberger, Christoph; Pflug, Lukas; Hübner, Holger; Buchholz, Rainer (Biotechnology and Bioprocess Engineering, 2012)
In this paper, a new Ansatz for modelling the Baculovirus infection cycle is presented. The base of this model is the cell cycle distribution at the time of infection. It is possible to calculate the growth of the culture and the initiation of virus processing by considering cell cycle distribution. By taking into account the length of the viral genome and the polymerase activity, it is possible to calculate the virus production rate, which underlies a logistic growth. In the present work, a new hypothesis explaining the accelerated death rates of infected cells has been introduced. This assumption provides the possibilities of performing calculation without any fixed time intervals. The simulation was tested by comparing experimental data with the model prediction. Therefore, cell cycle distributions over the culture time and the growth behaviour of infected and non-infected insect cells were measured. A model, Baculovirus coding for GFP was employed for the present investigation, as it allows tracking the infection and determining the effectiveness of the infection, which is highly dependent on the cell density at the time of infection (TOI). Furthermore, the new model is is taken to simulate data gained from literature about virus release and adsorption. The new assumptions make the model more independent to fit into different cultivation systems.
Keywords: baculovirus; modelling; insect cells; infection cycle

Comparative evaluation of the extracellular production of a polyethylene terephthalate degrading cutinase by Corynebacterium glutamicum and leaky Escherichia coli in batch and fed-batch processes - Fritzsche, Stefanie; Hübner, Holger; Oldiges, Marco; Castiglione, Kathrin (Microbial Cell Factories, 2024)
BACKGROUND: With a growing global population, the generation of plastic waste and the depletion of fossil resources are major concerns that need to be addressed by developing sustainable and efficient plastic recycling methods. Biocatalytic recycling is emerging as a promising ecological alternative to conventional processes, particularly in the recycling of polyethylene terephthalate (PET). However, cost-effective production of the involved biocatalyst is essential for the transition of enzymatic PET recycling to a widely used industrial technology. Extracellular enzyme production using established organisms such as Escherichia coli or Corynebacterium glutamicum offers a promising way to reduce downstream processing costs. RESULTS: In this study, we compared extracellular recombinant protein production by classical secretion in C. glutamicum and by membrane leakage in E. coli. A superior extracellular release of the cutinase ICCGDAQI was observed with E. coli in batch and fed-batch processes on a litre-scale. This phenomenon in E. coli, in the absence of a signal peptide, might be associated with membrane-destabilizing catalytic properties of the expressed cutinase. Optimisations regarding induction, expression temperature and duration as well as carbon source significantly enhanced extracellular cutinase activity. In particular, in fed-batch cultivation of E. coli at 30 °C with lactose as carbon source and inducer, a remarkable extracellular activity (137 U mL-1) and cutinase titre (660 mg L-1) were achieved after 48 h. Literature values obtained with other secretory organisms, such as Bacillus subtilis or Komagataella phaffii were clearly outperformed. The extracellular ICCGDAQI produced showed high efficacy in the hydrolysis of PET textile fibres, either chromatographically purified or unpurified as culture supernatant. In less than 18 h, 10 g L-1 substrate was hydrolysed using supernatant containing 3 mg cutinase ICCGDAQI at 70 °C, pH 9 with terephthalic acid yields of up to 97.8%. CONCLUSION: Extracellular production can reduce the cost of recombinant proteins by simplifying downstream processing. In the case of the PET-hydrolysing cutinase ICCGDAQI, it was even possible to avoid chromatographic purification and still achieve efficient PET hydrolysis. With such production approaches and their further optimisation, enzymatic recycling of PET can contribute to a more efficient and environmentally friendly solution to the industrial recycling of plastics in the future.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Autoinduction; Bioreactor; Cutinase; Enzymatic depolymerization; Extracellular; Lactose feed; Polyethylene terephthalate; Recombinant protein expression; Secretion

Measuring average rheological quantities of cell monolayers in the linear viscoelastic regime - Dakhil, Haider; Gilbert, Daniel; Malhotra, Deepika; Limmer, Anja; Engelhardt, Hannes; Amtmann, Anette; Hansmann, Jan; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver; Wierschem, Andreas (Rheologica Acta, 2016)
During the last decades, the rheology of cells has been studied almost entirely in single cells. While cell-to-cell variation is typically very large and most studies were carried out in the nonlinear viscoelastic regime, we quantify average linear viscoelastic cell properties like storage and loss moduli and normal stress in monolayers of different cell types showing that murine 3T6 fibroblasts, human fibroblasts, and HeLa cells differ considerably in their storage modulus. To this end, we modified a commercial rheometer to set up a parallel-disk configuration at gap widths of a few micrometers and optically detected the cell concentration in the gap. This enables studying the linear viscoelastic behavior of the cells and permits quantifying the impact of drugs affecting the cytoskeleton or the extracellular matrix connection. Thus, due to its high-content approach, without the need of treating the samples in the rheometer, this envisions the use of this method as a fast diagnostic tool. The method also allows for quantitatively studying of the impact of pre-stress on the storage and loss moduli of the cells.
Keywords: Cell rheology; Linear viscoelasticity; Narrow-gap rheometry; Parallel-disk configuration; Cell monolayer; Biochemical treatment; Pre-stress; Primary cells; Cell lines

Measuring the adhesion limit of fibronectin for fibroblasts with a narrow-gap rotational rheometer - Dakhil, Haider; Do, Hung; Hübner, Holger; Wierschem, Andreas (Bioprocess and Biosystems Engineering, 2018)
We study the adhesion limit of 3T6 fibroblasts, cultured in Dulbecco’s modified Eagle’s medium with 10% fetal bovine serum at 37 °C and 5% CO2, with a narrow-gap rotational rheometer in the parallel-disk configuration. Reducing the uncertainty in gap width to about 1 µm allows studying the cells at narrow gaps, which enables to study the critical shear stress of the cells in low-viscous media. The adhesion limit on fibronectin-coated glass plates is determined as a function of concentration and adhesion time. We found that cells in groups have a tendency to detach at slightly higher shear stresses than single cells. Moreover, 60 min after the settling phase are enough for the cells to adhere to the coated plate at maximum strength. We show that the setup may also be used for cells that are not adhered from suspension, but are grown directly on the substrate.
UnivIS-Import:2018-09-11:Pub.2018.tech.ITC.stmmec.measur
Keywords: Cell adhesion; Critical shear stress; Fibronectin concentration; Narrow-gap rheometry; Parallel-disk configuration

Prolonged Ex vivo expansion and differentiation of naïve murine CD43(-) B splenocytes - Zambrano, Kenny; Jerome, Valerie; Freitag, Ruth; Buchholz, Rainer; Jäck, Hans-Martin; Hübner, Holger; Schuh, Wolfgang; Buchholz, Rainer (Biotechnology Progress, 2016)
Ex vivo expansion of naive primary B cells is still a challenge, yet would open new possibilities for in vitro studies of the immune response or the production of monoclonal antibodies. In our hands, unstimulated murine B cells did not expand in significant numbers, while culture viability decreased rapidly within a few days. Activation mimicking in vivo stimulation through either T cell-independent or T-cell dependent signaling, led to several division cycles, albeit accompanied by irreversible differentiation. By co-culturing B cells under moderate hypothermia (30°C) on live feeder fibroblasts expressing recombinant CD40 ligand (CD154) and by repeatedly transferring cultured B cells to new feeder cell cultures, we could extend the growth of primary mouse B cells compared to cultures maintained at 37°C. B cells under these conditions showed an activated phenotype as shown by the presence of AID and IRF4, two factors required for IgH class switch recombination in antigen-activated B cells. In contrast to cells cultured at 37°C, B cells under hyperthermia did surprisingly not differentiate into Blimp-1 expressing plasmablasts. Thus, the repeated batch process under hyperthermic conditions represents a first step towards the development of a continuous cultivation system for the expansion of primary B cells. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:978-989, 2016.
EVALuna2:13639

Tetracycline-encapsulated P(3HB) microsphere-coated 45S5 Bioglass®-based scaffolds for bone tissue engineering - Meng, D.; Francis, L.; Thompson, I. D.; Mierke, Claudia; Hübner, Holger; Amtmann, A.; Roy, I.; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2013)
Bioglass®-based scaffolds for bone tissue engineering have been developed, which can also serve as carriers for drug delivery. For this, P(3HB) microspheres (PMSs) loaded with tetracycline were fabricated and immobilised on the scaffold surfaces by a modified slurry dipping technique. The sustained drug delivery ability in simulated body fluid was confirmed by using UV-Vis absorption spectroscopy measurements. The MTT assay using mouse fibroblast cells provided evidence that the tetracycline loaded microspheres produced in this study show limited cytotoxicity. The scaffolds developed in this work provide mechanical support, adequate 3D surface roughness, bioactivity and controlled drug delivery function, and are thus interesting candidates for bone tissue engineering applications. © 2013 Springer Science+Business Media New York.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.tetrac

The response of newly established cell lines of Spodoptera littoralis to group I and group II baculoviruses - Ahmed, Ibrahim Abdulla; Hübner, Holger; Mamoori, Yaseen Ismael; Buchholz, Rainer (Cytotechnology, 2019)
Autographa californica multiple nucleopolyhedrovirus (AcMNPV) and Spodoptera littoralis multiple nucleopolyhedrovirus (SpliMNPV) belong to group I and group II nucleopolyhedroviruses, respectively and can replicate in a wide range of insect species. In this study, the ability of newly established S. littoralis cell lines to support replication of AcMNPV and SpliMNPV was examined. The microscopic observations showed that the S. littoralis cells infected with AcMNPV exhibited morphological changes such as cells breaking into small bodies and forming apoptosis-like bodies post-infection. Nuclear DNA fragmentation was observed in all AcMNPV-infected cell lines through DNA gel electrophoresis analysis. Therefore, the virus replication was unsuccessful in most of cells, which were able to abort the virus replication. On the other hand, cells that were infected with SpliMNPV did not show similar morphological changes and no small bodies were formed. In addition, SpliMNPV succeeded to infect the cells, replicate, and form viral occlusion bodies inside the infected cells. In suspension culture, S. littoralis cells, which were infected with AcMNPV, accumulated as composed balls in shaker flasks after infection overnight, with cell density decreasing dramatically. In contrast, there was no cell clumping seen in the infected cells with SpliMNPV and the uninfected cells. In conclusion, the newly established embryonic S. littoralis cells were highly susceptible to SpliMNPV, whereas the cells were non-permissive to AcMNPV, yet they still underwent programmed cell death.
CRIS-Team Scopus Importer:2019-05-24
Keywords: AcMNPV; Apoptosis; SpliMNPV; Spodoptera littoralis

Viscoelastic Measurements of Cells in a Rotational Rheometer - Dakhil, Haider; Wierschem, Andreas; Gilbert, Daniel; Amtmann, Anette; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver (Chemie Ingenieur Technik, 2015)
UnivIS-Import:2018-09-11:Pub.2015.tech.ITC.cbiove.viscoe